Incorporating chamber ensembles in the middle school instrumental music program - Drennan, Heidi (Kansas State University, 2020)
As a band director, I recognize the learning opportunities that are presented by participation in chamber music ensembles. But ensemble playing is often confined to the small window of time during spring contest season for high school students. The ability to participate in small chamber ensembles can also be limited to students who are already excelling musically. Casual observations in my program have shown that students are motivated by their participation in these one-to-a-part groups, and the learning that takes place in the student-led rehearsals can benefit the larger ensemble. The feeling that students of all musical levels will benefit from participation in chamber ensembles led me to implement a chamber music program for my middle school students. The program began with a small ensemble project involving 8th-grade band members in the spring of 2020. The goal of this project is to expose students to the benefits of chamber ensemble participation and transfer their musical growth to the large ensemble experience. My teaching philosophies and practices have changed in several ways during the process of obtaining my master's degree. One of the most significant areas of growth has been in literature selection for my ensembles. The coursework exposed me to a variety of unfamiliar composers and has encouraged me to seek out different styles of music to share with my students. I have clarified many of the organizational aspects of my program, such as rehearsal design and sequence, assessments, and day to day management of the band. Reflecting on my personal music teaching theory and reviewing the work of significant music educational philosophers has allowed me to refine and focus my teaching goals and processes.
Keywords: Music education; Chamber ensemble; Middle school; Music; Band